Effects of an overnight high-carbohydrate meal on muscle glycogen after rapid weight loss in male collegiate wrestlers - Kondo, E.; Shiose, K.; Osawa, T.; Motonaga, K.; Kamei, A.; Nakajima, K.; Sagayama, H.; Wada, T.; Nishiguchi, S.; Takahashi, H. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background Severe rapid weight loss (RWL) induces a decrease in muscle glycogen (mGly). Nevertheless, adequate carbohydrate intake after RWL has not been reported to optimize muscle glycogen following a weigh-in the evening until a wrestling tournament morning. The purpose of this study was to investigate the effect of an overnight high-carbohydrate recovery meal of 7.1 g kg-1 following RWL on mGly concentration.